Managing the Implementation of Comprehensive Plans for Cities Master Plans, Using MCDM - عمران جمال; عبد الرحمن عباس; عيسى سحر (Latakia University Journal -Engineering Sciences Series, 2021)
Economically successful countries around the world tend to adopt spatially and socially integrated planning and implementation policies, as well as create institutions with high standards of life across all regions. Planning mechanisms include urban civilization, industrialization policies, and study of changing spatial population distribution and production, related to a quite-studied spatial planning, especially at the level of general organizational plans (Master plan). Syria faces a major challenge in overcoming population concentration phenomenon and production in specific areas, especially after a big deterioration of the country’s urban infrastructure, also in light of increase the studies frequency, projects and improvised initiatives related to reconstruction process, which impedes a development balance as a result of geographical disparities. In addition to the implementation deviation of organizational plans from objectives, resulting from absence of application methodologies, led to plans that are not applicable, therefore random in development processes that negatively affect all aspects of life, as well as economic development, rational management of planning in Syrian cities also at various social, economic and service levels. The research deals with a comprehensive study of factors affecting the deviation of organizational schemes from their role in managing development process. A methodology has been developed to support multi-criteria decision-making in addition to ensure application of comprehensive plans in Master plans, and activate comprehensive planning management of these, especially in reconstruction process. Taking advantage of global experiences to achieve state’s goals in integrated, directed and sustainable development, a scientific methodology based on MCDM, with appropriate means and techniques in Syrian institutions to achieve the aspirations of different social groups.